Melittin suppresses epithelial–mesenchymal transition and metastasis in human gastric cancer AGS cells via regulating Wnt/BMP associated pathway. Issue 11 (4th September 2021) - Huang, Jye-Yu; Peng, Shu-Fen; Chueh, Fu-Shin; Chen, Po-Yuan; Huang, Yi-Ping; Huang, Wen-Wen; Chung, Jing-Gung
ABSTRACT: Gastric cancer has a poor prognosis; once cancer has metastasized, it can easily lead to patient death. Melittin is one of the major components extracted from the bee venom. It has been shown that melittin emerges antitumor activities against many human cancer cell lines. Our results indicated that melittin at 0.2-0.5 µm significantly reduced total cell viability in human gastric cancer AGS cells. At low concentrations (0.05-0.15 µm ), melittin displayed antimetastasis effects and inhibited cell adhesion and colony formation. Besides, it inhibited cell motility and suppressed cell migration and invasion. Melittin inhibited the activities of MMP-2 and MMP-9 and the integrity of cell membrane in AGS cells. Furthermore, Western blotting results showed that melittin decreased the protein expressions of Wnt/BMP and MMP-2 signaling pathways. Based on these observations, melittin inhibited cell migration and invasion of AGS cells through multiple signaling pathways. It may be used to treat metastasized gastric cancers in the future. Graphical Abstract: